(3JGQjN GdadSaI GdMOjKI (B/s - (3cQe, jhSas ((3GdOeGe (B[(3GdSYhOjI(B]:s (3GdQjGV(B[(3GdSYhOjI(B]:s (3LOI (B[(3GdSYhOjI(B]:s (3ecJHI GdeJfHj,s, 2019)
(3jYJHQ cJGH JGQjN GdadSaI GdMOjKI Edi LGfH chfg jDQN ddadSaI GdMOjKI GdJj XgQJ HYO adSaGJ GdYUQ GdhSjW eYLeG adSajG jOdfG aj hVhM hjSQ Ydi QLGd GdadSaI efP GdbQf GdNGeS YTQ MJi ChGFd GdbQf GdYTQjf hjOhQ GdHGH GdChd aj GdcJGH Yf HbGjG GdadSaGJ GdbOjeI ajJMOK Yf GdCadGWhfjjf GdPjf jSJeOhf efg CSHGH Ojf WHjYj hGdQTOjhf GdPjf jPjYhf GdEdMGO JMJ SJGQ OQGSI CQSWh hGHf QTO hjJMOK GdHGH GdKGfj Yf CegGJ GdePGgH GdMOjKI eKd ePGgH OjcGQJ hHScGd hSHjfhRG Ke jJMOK Yf aSdaGJ GdhGbYjI hQLGdgG eKd gjhe hHjchf aj GdHGH GdKGdK haj GdHGH GdQGHY jYQV dadSaGJ ejf Oj HjQGf hChLSJ chfJ GdJj JMGhd GSJjYGH LejY GdfhGMj aj ePgH hGMO Ke jQUO aj GdHGH GdNGeS GdUQGY Hjf OGQhjf hSHfSQ hCfUGQ GdeGOjI GdPjf hLOhG aj fXQjI GdJWhQ CSdMI LOjOI hHjf GdQhMjI GdJj jDjOgG GdaQfSjhf Ke jJVM aj GdaUd GdCNjQ GdGfbSGe GdcGed Hjf GdadSaGJ GdMOjKI Edi ePgHjf eGOj hQhMj jJUGQYGf HTcd OGFe HMKG Yf Mdhd(B.s
(3cTGa (B: (3UaMI (B513-516.s
(3JUeje GdZdGa (B: (3CSGeI Wg(B.s
(3HHdjhLQGajI (B: (3UaMI (B509-512.s
Keywords: (3GdadSaI GdMOjKIs -- (3JGQjNs